2012
DOI: 10.1136/flgastro-2012-100184
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal surgery in adult patients with cystic fibrosis

Abstract: Objective Gastrointestinal conditions requiring surgical intervention are becoming increasingly frequent in adults with cystic fibrosis (CF) as life expectancy increases. In addition, patients with CF are at risk of specific gastrointestinal complications associated with their disease. This includes distal intestinal obstruction syndrome (DIOS), which may affect up to 15% of patients, and can present diagnostic and therapeutic challenges. The aim of this study was to determine the nature and frequency of gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A 2012 UK study reported on 377 patients in an effort to characterize outcomes for adult CF patients undergoing GI surgery. 12 Sharma et al identified DIOS, biliary disease, and gastroesophageal reflux as the most common indications for surgery. Of patients operated on for DIOS ( n = 11), there was no mortality, although 3 had prolonged hospitalization due to respiratory complications.…”
Section: Discussionmentioning
confidence: 99%
“…A 2012 UK study reported on 377 patients in an effort to characterize outcomes for adult CF patients undergoing GI surgery. 12 Sharma et al identified DIOS, biliary disease, and gastroesophageal reflux as the most common indications for surgery. Of patients operated on for DIOS ( n = 11), there was no mortality, although 3 had prolonged hospitalization due to respiratory complications.…”
Section: Discussionmentioning
confidence: 99%
“…In noncirrhotic CFLD, the predominant clinical manifestations are at least one of the following: (1) elevation of AST, ALT, and GGT more than twice the upper limit of normal, (2) hepatic steatosis (liver parenchyma hyperechogenicity and poor penetration on US, decreased attenuation on CT, or signal dropout on chemical shift MRI sequences), (3) hepatic fibrosis (histologic diagnosis), or (4) cholangiopathy (beading and strictures of the biliary system on US, MRI, CT, or ERCP) [7, 8, 17, 2123]. In advanced cases, CFLD can progress to focal biliary cirrhosis and multilobular diffuse cirrhosis (small-size liver, nodular hepatic contour, and coarse heterogeneous parenchyma) with or without portal hypertension (splenomegaly, abdominal varices, and ascites) [17, 18, 20, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Intussusception occurs in 1–2% of patients with CF and appears to occur more frequently in those with DIOS, with published rates of up to 25%. It is usually ileocolic and can subside spontaneously …”
Section: Complicationsmentioning
confidence: 99%
“…Recurrence rates for DIOS range from 33% to 81% . The rates of DIOS and recurrence are increasing, likely related to increasing the lifespan of adults with CF …”
Section: Complicationsmentioning
confidence: 99%